2021
DOI: 10.1016/j.psj.2021.101246
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore-based full-length transcriptome sequencing of Muscovy duck (Cairina moschata) ovary

Abstract: Unlike mammals, studies on mechanisms that regulate waterfowl ovulation have been rarely reported. To advance our understanding of the ovulation differences in Muscovy duck, we utilized the Oxford Nanopore Technologies ( ONT ) to generate transcriptome data from 3 groups of female duck ovaries with ovulation differences (i.e., preovulation [ PO] , consecutive ovulation [ CO ], and inconsecutive ovulation [ IO ]). In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 78 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…Using RNA-seq short reads to correct the low-quality isoforms generated by ICE proofread, and then combined the corrected low-quality isoforms and high quality isoforms into the full-length isoforms. In ISO-seq analysis, multiple different isoforms may be generated from the same transcript, and these may also be assigned to different libraries, using TOFU software ( https://github.com/PacificBiosciences/cDNA_primer/wiki/What-is-pbtranscript-tofu%3F-Do-I-need-it%3F ) to remove the redundant isoforms [ 41 ]. Finally, sequences with a coverage less than 0.85 and identity less than 0.9 were filtered, merged only the 5'-end exon with the difference in alignment, and obtained 24,658 non-redundant transcript sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Using RNA-seq short reads to correct the low-quality isoforms generated by ICE proofread, and then combined the corrected low-quality isoforms and high quality isoforms into the full-length isoforms. In ISO-seq analysis, multiple different isoforms may be generated from the same transcript, and these may also be assigned to different libraries, using TOFU software ( https://github.com/PacificBiosciences/cDNA_primer/wiki/What-is-pbtranscript-tofu%3F-Do-I-need-it%3F ) to remove the redundant isoforms [ 41 ]. Finally, sequences with a coverage less than 0.85 and identity less than 0.9 were filtered, merged only the 5'-end exon with the difference in alignment, and obtained 24,658 non-redundant transcript sequences.…”
Section: Resultsmentioning
confidence: 99%
“…So far, ONT long-read transcriptomics has been used with one other species that did not have a species-speci c reference database available (the Muscovy duck). However, in that study, the authors used a reference database from a different genus, and characterized well-established and conserved genes (Lin et al, 2021). In contrast, our genes of interest are rapidly evolving, often species-speci c genes from AG of males insects, and we successfully discover more than two dozen novel genes that are found only in S. punctum (Figure 4b).…”
Section: Discussionmentioning
confidence: 99%
“…However, in non-model species without reference databases, the uptake of ONT long-read transcriptomics has been negligible and there are no studies comparing ONT transcriptomics with other sequencing platforms (e.g., Illumina, PacBio). In fact, a search for ONT transcriptomics of lesser-studied species led us to just one publication on the Muscovy duck where a database from an alternate duck species was used as a reference (Lin et al, 2021) (search conducted on 8th September 2021). The combination of lack of reference databases and high sequencing error rates, makes it especially challenging to undertake de novo ONT transcriptomics (Sahlin et al, 2021;Sahlin & Medvedev, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In order to track the change process of the metabolome more deeply, we join the transcriptome for multi-omics joint analysis. Previous transcriptomics data showed that a total of 3,046 DEGs (1,046 up-regulated and 2,000 down-regulated) were identified in the PO compared with the CO group (18). A comprehensive analysis of metabolomics and transcriptomics was performed, and 55 Co-enriched pathways were derived (Figure 4), the lipid metabolism-related pathways were dramatically changed, of which we focused on three pathways including Arachidonic Acid metabolism, Glycerophospholipid metabolism and Steroid hormone biosynthesis pathways.…”
Section: Integrated Analysis Of Metabolomics and Transcriptomicsmentioning
confidence: 99%